Oribatid mites (Acari, Oribatida) of steppe vegetation on cape Tarhankut in Crimea (Ukraine) - Seniczak, Stanisław; Kaczmarek, Sławomir; Seniczak, Anna (Biological Letters, 2010)
Oribatid mites were investigated in patches of steppe vegetation, dominated by esparto (Stipa sp.), other grasses, Artemisia caucasica, Sedum sp., mosses, or lichens, on cape Tarhankut in Crimea (Mediterranean climate). These mites were quite abundant and rich in species there, probably thanks to the fresh sea breeze and geographic expansion of species from the Mediterranean region, Central Asia, and Europe. They achieved the highest density in patches of steppe grasses other than esparto, but most species occurred in sedum patches. The most abundant was Tectocepheus velatus, especially in patches of steppe grasses other than esparto, and relatively abundant were Scutovertex sp. 1, Jacotella neonominata and Scheloribates laevigatus. In populations of these species the adults usually dominated, but their age structure greatly depended on vegetation type.